Legal Protection Duties on Notary Positions if Malpractice Happen in the Making of Authentic Deals - Jane Florin Merietta; Djunaedi Djunaedi (Sultan Agung Notary Law Review, 2022)
This legal research aims to identify and analyze the juridical consequences and responsibilities of a Notary if a Notary commits malpractice while carrying out his duties as a Notary, as well as to find out and analyze the extent of legal protection for the duties of a Notary's office who are suspected of having committed malpractice in making authentic deeds. This study uses a sociological juridical approach using descriptive analytical research specifications. The type of data in this legal research uses primary legal materials and secondary legal materials, as well as tertiary legal materials. The data collection method in this study is in the form of literature and the data analysis method used is qualitative data analysis. Based on the results of research and discussion, that if a Notary commits a malpractice against his authentic deed, then the authentic deed is relegated to a private deed. Then, legal protection for Notaries who commit acts of malpractice must involve professional organizations or INI as a forum that can educate and solve problems that exist among its members.